Justice blindfolded: the historical course of an image - Prosperi, Adriano (Catholic Christendom, 1300-1700 Ser, 2018)
Intro -- Contents -- Preface to the Italian Edition -- Preface to the English Edition -- Figures -- Chapter 1 -- Scale and Sword, Eyes and Blindfold: the Attributes of Justice -- Chapter 2 -- Justice, That is to Say God -- Chapter 3 -- The Blindfold -- Chapter 4 -- Jesus, Barabbas and the Good Thief -- Chapter 5 -- Justice and Grace -- Chapter 6 -- Miracles and Salvation -- Chapter 7 -- The Divine Eye of the Law -- Chapter 8 -- Changes in Symbols -- Chapter 9 -- The Veil of Justice and the Risks of the Limelight -- Select Index of Names